Getting It "Right": Ensuring Informed Consent for an Online Clinical Trial. (October 2016) - Barrera, Alinne Z.; Dunn, Laura B.; Nichols, Alexandra; Reardon, Sonia; Muñoz, Ricardo F.
Ethical principles in conducting technology-based research require effective and efficient methods of ensuring adequate informed consent. This study examined how well participants understood the informed consent form for an online postpartum depression trial. Pregnant women ( N = 1, 179) who consented to the trial demonstrated an understanding of the purpose (86.1%) and procedures of the study (75.8%), and the minimal risks associated with answering sensitive questions online (79%). Almost all (99.6%) understood that psychological treatment was not offered. Participants with current depression incorrectly indicated that participation would replace current psychological treatment relative to participants with a lifetime or no depression history (19.6% vs. 13.5 % vs. 10.4%, respectively) and that there were no associated risks with participation (29.6% vs.17.6% vs. 16.7%, respectively). Findings provide initial evidence that most individuals who seek online psychological resources are informed consumers.